Thromboembolism in inflammatory bowel diseases: a report from Saudi Arabia - Hussain Issa (Clinical and Experimental Gastroenterology, 2011)
Hussain Issa1, Sami Al-Momen1, Bahaa Bseiso1, Ghada Ali Al-Janobi1, Mohamad Al-Jama1, Fadel Ali Almousa1, Mahdi E Al-Jarodi1, Ahmed H Al-Salem21Department of Internal Medicine, King Fahad Specialist Hospital, Dammam, Saudi Arabia; 2Department of Pediatric Surgery, Maternity and Children Hospital, Dammam, Saudi ArabiaAbstract: Thromboembolism (TE) is a serious but under-recognized complication of inflammatory bowel disease (IBD). This is specially so in developing countries where the incidence of IBD is low. In Saudi Arabia, IBD is considered to be rare, but the incidence is increasing. Where the clinical manifestations resemble those of developed countries, TE as a complication of IBD is considered to be very rare. This report describes six IBD patients with TE. This importance of the complication of TE is stressed, and physicians caring for these patients should be aware of it in order to obviate potential morbidity and mortality.Keywords: thromboembolism, inflammatory bowel disease, Crohn's disease, ulcerative colitis